DELIVERY OF HEALTH CARE SERVICES TO THE UNDERPRIVILEGED COMMUNITIES”: A DREAM TO BE REALIZED - Muhammad Saeed (Journal of University Medical & Dental College, 2020)
Our governments have been spending millions of rupees to provide health care services to all segments of population starting from big cities to towns and far flung rural places .The sufficiency of these provisions or otherwise may be questioned but it still remains the most important source to fulfill the health care needs of a common man in all parts of the country.*